2014
DOI: 10.1039/c4cp01159g
|View full text |Cite
|
Sign up to set email alerts
|

An insight into structure and stability of DNA in ionic liquids from molecular dynamics simulation and experimental studies

Abstract: Molecular dynamics simulation and biophysical analysis were employed to reveal the characteristics and the influence of ionic liquids (ILs) on the structural properties of DNA. Both computational and experimental evidence indicate that DNA retains its native B-conformation in ILs. Simulation data show that the hydration shells around the DNA phosphate group were the main criteria for DNA stabilization in this ionic media. Stronger hydration shells reduce the binding ability of ILs' cations to the DNA phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
75
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 64 publications
(80 reference statements)
14
75
1
Order By: Relevance
“…1 (a, b) and [24,27]. Micaelo and co-workers [27] showed enhancement in emission intensity when an IL is added to the solution containing DNA-bound pyrene, which was attributed to the space constraints imposed due to the electrostatic interaction between DNA and IL, resulting in the release of pyrene into the solution and hence enhanced emission intensity. However, in the present study, we found that the intensity of the DNA-bound pyrene remained almost unchanged even after the addition of cholinium based ILs.…”
Section: Absorption and Fluorescence Studymentioning
confidence: 96%
See 1 more Smart Citation
“…1 (a, b) and [24,27]. Micaelo and co-workers [27] showed enhancement in emission intensity when an IL is added to the solution containing DNA-bound pyrene, which was attributed to the space constraints imposed due to the electrostatic interaction between DNA and IL, resulting in the release of pyrene into the solution and hence enhanced emission intensity. However, in the present study, we found that the intensity of the DNA-bound pyrene remained almost unchanged even after the addition of cholinium based ILs.…”
Section: Absorption and Fluorescence Studymentioning
confidence: 96%
“…Combining these two, several articles have been published describing the interaction of DNA with imidazolium, morpholinium, etc. based ILs [21][22][23][24][25][26][27][28][29]. For example, Liu and co-workers studied the impact of alkyl chain length present on imidazolium-based ILs [23] towards ct-DNA through extensive photophysical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the ct-DNA interact pyrene with higher binding constant in excited state than CTAB. It is well known that there are intercalations of pyrene with DNA bases at the grooves [21,22]. where free pyrene would no more available, suffered a systematic quenching with the increasing concentration of CTAB in the solution, as shown in Fig.…”
Section: Steady State Emission Studymentioning
confidence: 97%
“…PVDF molecules used in this simulation consists of 7 monomers [19]. 1,3-dialkylimidazolium bromide IL was selected as the simulation ILs [20]. The structure of water can be found in the library of GROMACS package.…”
Section: Methodsmentioning
confidence: 99%
“…This method makes the calculation cheap and simple. Recent research focus on composite membrane of PVDF to investigate the possibility of increasing the performance of the material in term of reliability and anti-erosion properties [4,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%